Bone mass and somatic development in young female gymnasts: A longitudinal study - Courteix, D.; Jaffre, C.; Obert, P.; Benhamou, L. (Pediatric Exercise Science, 2001)
The aim of this study was to assess the effects of vigorous activity on the somatic and skeletal growths in young females reaching puberty. From a group of 41 prepubertal girls, 24 remained in this study: 10 gymnasts training 15 to 22 hr a week and 14 non-exercising controls. At the start and during the study period, bone age, height, weight, fat and lean mass were significantly lower in the gymnasts vs. the controls (p < .05). These variables had increased in the same way for both groups. At each investigation, the gymnasts had significantly higher BMC, BMD, and BMAD at all the sites (p < .01) except the whole body. The strong correlation between somatic measurements at the start and at the end of the study indicated that physical exercise does not disrupt the normal growth in these children.